How to Structure Reader’s Workshop to Make Learning Visible to Both Teacher and Student - Filiatreaux, Addison (My University, 2017)
This study focused on how to structure conferring during reader’s workshop. It took place in a Twin Cities suburb over the course of nine weeks in an 8th grade classroom. Students and staff were already familiar with reader’s workshop because it was implemented in the district three years ago. During the study, there were four main types of conferences that were addressed: reading habits, skills based, reading log, and monthly reflection conferences. Incorporating different conference styles helps teachers set up an organized method of conferring, so learning is visible to both teacher and student. This study used qualitative methods including observations of students reading, reading habits surveys, conferring notes, formative assessments of Post-It thinking stacks, learning targets, and student reflections. This study yielded the ability to meet with significantly more students than without the structured workshop, and students felt that they had grown more than they had in previous years.